Thermoelectric Energy Harvesting for Building Energy Management Wireless Sensor Networks - Wensi Wang; Victor Cionca; Ningning Wang; Mike Hayes; Brendan O'Flynn; Cian O'Mathuna (International Journal of Distributed Sensor Networks)
A thermoelectric energy harvester powered wireless sensor networks (WSNs) module designed for building energy management (BEM) applications is built and tested in this work. An analytic thermoelectric generator (TEG) electrical model is built and verified based on parameters given in manufacturer data sheets of Bismuth Telluride TEGs. A charge pump/switching regulator two-stage ultra-low voltage step-up DC/DC converter design is presented in this work to boost the <0.5 V output voltage of TEG to usable voltage level for WSN (3.3 V). The design concept, device simulation, circuits schematic, and the measurement results are presented in detail. The prototype device test results show 25% end-to-end conversion efficiency in a wide range of input temperatures/voltages. Further tests demonstrate that the proposed thermoelectric generator design can effectively power WSN module which operates with a 1.7% duty cycle (5.8 seconds measurement time interval) when the prototype is placed on a typical wall-mount heater (60°C surface temperature). The thermoelectric energy harvesting powered WSN demonstrates duty cycles significantly higher than the required duty cycle for BEM WSN applications.